Social Media Marketing, Electronic Word of Mouth, and Trust in TikTok Shop Purchase Decisions - Dedi, Selmi; Ramadhani, Andini Putri Sari; Saptomo, Yulius Heri; Sudarwadi, Dirarini; Malino, Marlina; Sumari, Jenita (Jurnal Manajemen Bisnis, 2026)
This study investigates the effects of social media marketing and electronic word-of-mouth on purchase decisions in TikTok Shop, with trust as an intervening variable. The study addresses the limited emphasis on purchase decision in social commerce research and tests whether brand-generated and user-generated communication significantly shape consumer decision-making. The study employed a quantitative explanatory design using an online survey of 105 Generation Z respondents in Manokwari Regency who had previously purchased through TikTok Shop. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling to examine direct and indirect relationships among social media marketing, electronic word of mouth, trust, and purchase decision. The results show that social media marketing and electronic word-of-mouth both have positive and significant effects on trust and purchase decisions. Social media marketing exerts the strongest influence on trust, whereas electronic word of mouth has a stronger direct impact on purchase decisions. Trust also significantly affects purchase decisions and partially mediates both antecedent variables. The findings highlight that the purchase decision on TikTok Shop is shaped by the interaction among persuasive platform communication, peer evaluation, and consumer confidence, offering practical guidance for trust-oriented social commerce strategies and further research on decision behavior.